Analisis Upaya Guru dalam Mengatasi Kesulitan Belajar Matematika Siswa dalam Materi Bangun Datar (Layang-Layang dan Trapesium) di Kelas IV SDN Kalideres 05 Pagi - Unaenah, Een; Septianih, Nabilah; Aryanih, Eka; Ayanih, Ayanih (ARZUSIN, 2022)
This study aims to describe the efforts made by the teacher to overcome the mathematical difficulties experienced by students in the area and circumference of a kite and trapezoid in grade IV SDN Kalideres O5 Pagi. The subjects of this study were students who had difficulty learning mathematics on the area and perimeter of kites and trapezoids, as well as classroom teachers. Collecting data using interview techniques and direct observation. The results showed that students had difficulty learning on the subject of the area and circumference of a kite and trapezoid. Difficulties experienced by students are difficulty determining formulas, misunderstandings about story problems, incorrect use of place values, errors in calculating the area and perimeter of kites and trapezoids. The teacher's efforts in overcoming the difficulties of learning mathematics on the area and perimeter of the kite and trapezoid flat shapes by paying special attention to students, tutoring such as mathematical symbols, place values, the concept of area and perimeter of kites and trapezoids, remedial learning, motivate students in study.